Magnetic device including Heusler compound and method of providing a magnetic device
By using the alternating structure of MN nitride and CO-AL as a chemical template layer in the MRAM device, it promotes the growth of the Hessler compounds, solves the problem of insufficient heterosexuality in the interface, and realizes the height of the ultra-thin Hrsler membrane. Quality growth and high density storage of MRAM devices.
Patent Information
- Application Number
- CN201910096762.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-31
- Filing Date
- 2019-01-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2039-01-31
AI Technical Summary
When existing MRAM devices shrink to sizes below ~20nm, the interface anisotropy is insufficient, resulting in thermal fluctuations affecting the switching performance, making it difficult to achieve high-density storage.
The alternating structures of the MN nitride (MNXN) layer and the CO-AL layer are used as the chemical template layer to promote the growth of the Hessler compound, forming a ultra-thin film with high vertical magnetic heterosexuality.
Achieve high -quality ultra -thin Hasler membrane growing on amorphous or polycrystalline substrates, with excellent magnetic properties and thermal stability, support the reduction of MRAM devices and high density storage.
Smart Images

Figure CN110350082B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of magnetic random access memory (MRAM), and more particularly, to the field of MRAM devices that rely on spin transfer torque. Background Art
[0002] Magnetic tunnel junctions (MTJs) form the basic storage element of new non-volatile magnetic random access memories (MRAMs) that promise high performance and endurance and have the potential to be scaled down to extremely small sizes. Magnetic tunnel junctions (MTJs) consist of a sandwich structure of two magnetic electrodes separated by an ultra-thin insulating layer. One of these layers forms the memory or storage layer, the other forms a reference layer whose magnetic structure does not change during the operation of the MRAM. The current tunneling between the reference and storage magnetic electrodes is spin-polarized: the magnitude of the spin polarization is determined by a combination of the electronic properties of the magnetic electrodes and the "spin filtering" properties of the tunnel barrier.
[0003] In current MRAM, the magnetic state of the MTJ is changed by passing an electric current through the MTJ, regardless of whether the magnetization orientation of the electrode forming the storage layer is parallel or antiparallel to the magnetization of the reference electrode. The intrinsic spin-polarized current transfers spin angular momentum, which, once the threshold current is exceeded, causes the direction of the torque of the magnetic storage electrode to switch. This transfer of spin angular momentum produces spin transfer torque (STT), and the magnetic storage electrode switched by this method is called STT-MRAM. When the magnetization of the electrode is perpendicular to the layer orientation, the magnitude of the switching current is reduced. The magnitude of this current is limited by the size of the transistor used to provide the write current. This means that the thickness of the switchable magnetic electrode (storage electrode) must be small enough so that it can be switched by the available current. Therefore, for ~1000emu / cm 3 To obtain a magnetization value of 0.0040 W, the electrodes must have a thickness of no more than about 1 nm.
[0004] The most promising materials being explored today for MTJs for dense MRAM include ferromagnetic electrodes formed from an alloy of Co, Fe, and B, and tunnel barriers formed from MgO (see Parkin patent). The ferromagnetic electrodes are made thin enough so that the magnetization of these electrodes is oriented perpendicular to the layers. The perpendicular magnetic anisotropy (PMA) of the Co-Fe-B layers comes from the interface between these layers and the tunnel barrier and / or the underlying layer on which the Co-Fe-B layer is deposited. Therefore, these layers must be made thin enough so that the interface PMA overcomes the demagnetization energy, which comes from the magnetic mass and increases proportionally with the magnetic mass of the Co-Fe-B layer. In practice, this means that when the device size is reduced to a size below ~20nm, the PMA is too weak to overcome thermal fluctuations because the thickness of the magnetic layer must be less than the thickness required to keep its moment perpendicular and less than the thickness required to switch the magnetic layer at a reasonable current density. So far, the magnetic materials whose magnetic moments can be switched by STT in MRAM devices have interface anisotropy, shape anisotropy, or no anisotropy. Such materials do not allow MRAM devices to be scaled down to sizes below ~20 nm. New materials are needed for ferromagnetic electrodes that exhibit a much greater PMA than that exhibited by Co-Fe-B and preferably that PMA comes from the volume or size of the electrode. A promising class of magnetic materials with this property is Heusler compounds. Heusler alloys are compounds with the chemical formula X 2 Compounds of X, X', X" and Y are transition metals or lanthanides (rare earth metals) and Z is from a main group metal. Heusler compounds have Cu (as defined in the Pearson table) 2 MnAl type structure in which the elements are arranged on 4 interlaced face-centered cubic (fcc) lattices. Many compounds (~800) are known in this family (T. Grafet. al., Progress in Sol. State Chem. 39, 1 (2011)). Some of these compounds are ferromagnetic or ferrimagnetic due to the magnetic moments at the X and / or Y sites. In addition, although the parent Heusler compound is cubic and exhibits weak or insignificant magnetic anisotropy, the structures of some of these compounds are also found to be tetragonally deformed: due to this deformation, the magnetization exhibited by these compounds can be preferably aligned along the tetragonal axis. Therefore, films formed from this material can exhibit PMA due to the magnetocrystalline anisotropy associated with its tetragonal deformed structure. Some known examples of such tetragonal Heusler compounds are Mn 3 Z (where Z = Ga, Ge, Sn and Sb) or Mn 2 CoSn. So far, the conductive underlayer has been used on Si / SiO 2 The thickness of the magnetic electrode formed by the Heusler alloy on the substrate is far more than 1 nm. The thinnest layer to date is used for the Heusler compound Mn3 Ge, for the Heusler compound Mn 3 Ge, layers as thin as 5 nm show perpendicular magnetic anisotropy and reasonably square hysteresis loops. Ultrathin films (~1 nm thick) of these materials that exhibit large PMAs grown on chemical template layers (CTLs) require the use of single-crystalline substrates such as MgO(100) or on Si / SiO 2 A MgO seed layer is used on the substrate. Such a single crystalline substrate or the use of MgO as part of the seed layer is not useful for STT-MRAM applications, where the MTJ must be deposited on wires formed of polycrystalline copper in today's CMOS-based technology, which may be covered with other layers that are also polycrystalline or amorphous. In order to be able to use ultra-thin tetragonal Heusler compounds as magnetic electrodes switchable by STT for MRAM, methods of forming these compounds on amorphous or polycrystalline substrates or layers are needed. Summary of the invention
[0005] A magnetic device is described. The magnetic device includes a substrate, a Mn covering the substrate x N layer, a multilayer structure that is nonmagnetic at room temperature, and a first magnetic layer. Mn x The N layer has 2≤x≤4.75. The multilayer structure includes alternating layers of Co and E, wherein E includes at least one other element including Al. The composition of the multilayer structure is Co 1-x E x It indicates that x is in the range from 0.45 to 0.55. The first magnetic layer includes a Heusler compound. The first magnetic layer is in contact with the multilayer structure, and the first magnetic layer forms a part of a magnetic tunnel junction.
[0006] A method for providing a magnetic device is described. The method includes using the magnetic device as a storage element, the magnetic device comprising: a substrate, a Mn covering the substrate x N layer, a multilayer structure that is nonmagnetic at room temperature, a first magnetic layer, a tunnel barrier, and a second magnetic layer in contact with the tunnel barrier. x The N layer has 2≤x≤4.75. The multilayer structure includes alternating layers of Co and E, wherein E includes at least one other element including Al. The composition of the multilayer structure is Co 1-x E x Indicates that x is in the range of from 0.45 to 0.55. The first magnetic layer includes a Heusler compound. The first magnetic layer is in contact with the multilayer structure, and the first magnetic layer forms part of a magnetic tunnel junction. The tunnel barrier covers the first magnetic layer so as to allow current to pass through both the tunnel barrier and the first magnetic layer.
[0007] A magnetic device is described. The magnetic device includes a substrate, a multilayer structure that is nonmagnetic at room temperature, a first magnetic layer, a tunnel barrier covering the first magnetic layer, and a second magnetic layer in contact with the tunnel barrier. The multilayer structure includes alternating layers of Co and E, wherein E includes at least one other element including Al. The composition of the multilayer structure is Co 1-x E x Indicates that x is in the range of from 0.45 to 0.55. The multilayer structure covers the substrate. The first magnetic layer includes a Heusler compound. The first magnetic layer is in contact with the multilayer structure. The second magnetic layer has a switchable magnetic moment. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 :For different N in the sputtering gas 2 Mn:N ratio of the as-grown Mn nitride films determined by RBS.
[0009] Figure 2 :Measurement of Mn grown at different temperatures 4 The root mean square roughness r of N film rms .
[0010] Figure 3 : RMS roughness r of MnN films as a function of Mn / N ratio rms and resistivity.
[0011] Figure 4 : Mn x Out-of-plane X-ray diffraction θ-2θ scans of N film with x=1, 2, 3, 3.76, 4 and 4.75.
[0012] Figure 5 :Depend on Figure 4 The XRD data shown in x Out-of-plane lattice constant of N film.
[0013] Figure 6 : Mn x N / Out-of-plane X-ray diffraction θ-2θ scans of CoAl layer with x=1, 2, 3, 3.76, 4 and 4.75.
[0014] Figure 7 : Measured in the as-deposited state and after annealing at 300℃ for 30 minutes. Mn x N / CoAl layer Mn 3P-MOKE hysteresis loops of Sb Heusler compounds with x = 1, 2, 3, 3.76, 4 and 4.75.
[0015] Figure 8 : The results of the as-deposited state and after continuous annealing at 300℃, 350℃ and 400℃ for half an hour in an applied field of 1T on Mn with various thicknesses 3 Coercivity of the P-MOKE hysteresis loop measured for Ge Heusler compounds.
[0016] Fig. 9 : Schematic diagram of a typical MTJ device stack deposited on a CIPT substrate.
[0017] Fig.10 :right Fig. 9 VSM hysteresis loops measured for the stack described in .
[0018] Fig.11 : Plot of MTJ device conductance versus device area. The solid line shows the linear least squares fit to the conductance data.
[0019] Fig.12 : Transmission electron microscopy (TEM) image of a cross-sectional view of a representative MTJ device shown in the left inset. This area is imaged at high resolution. The inset in the lower right corner shows an expanded view of this area.
[0020] Fig.13 : Device resistance (R) versus applied field (H) for an MTJ with 110 nm (nominal) diameter.
[0021] Fig.14 :For Fig.12 The resistance (R) vs. bias voltage for the same MTJ device used in Figure 1. The schematic on the right describes the electrical connections to the device.
[0022] Fig.15 : Switching probability measured as a function of the duration of the voltage pulse in nanoseconds. The schematic on the right describes the electrical connections to the device.
[0023] Fig.16 : Relationship between the switching current and the duration of the voltage pulse (left). The dependence of the switching current on the inverse of the voltage pulse duration is plotted on the right. DETAILED DESCRIPTION
[0024] Exemplary embodiments relate to magnetic junctions that can be used in magnetic devices such as magnetic memories, and devices using such magnetic junctions. Magnetic memories may include spin transfer torque magnetic random access memory (STT-MRAM), spin orbit coupling torque (SOT) memory, and may be used in electronic devices using non-volatile memory. Other devices including magnetic junctions, especially STT or SOT programmable magnetic junctions, include, but are not limited to, logic, neuromorphic computing units, and other devices. Electronic devices include, but are not limited to, cellular phones, smart phones, tablet computers, laptop computers, and other portable and non-portable computing devices. The following description is given to enable a person of ordinary skill in the art to make and use the present invention, and is provided in the context of patent applications and their requirements. Various modifications to the exemplary embodiments and the general principles and features described herein will be readily apparent. The exemplary embodiments are described primarily in terms of specific methods and systems provided in specific implementations. However, these methods and systems will operate effectively in other implementations. Phrases such as "exemplary embodiments", "one embodiment", and "another embodiment" may refer to the same or different embodiments and multiple embodiments. The embodiments will be described with respect to systems and / or devices having certain components. However, the system and / or device may include more or fewer components than those shown, and changes in the arrangement and type of components may be made without departing from the scope of the invention. The exemplary embodiments will also be described in the context of a particular method with certain steps. However, the method and system operate effectively for other methods with different and / or additional steps and steps in different orders that do not contradict the exemplary embodiments. Therefore, the present invention is not intended to be limited to the embodiments shown, but is intended to conform to the widest scope consistent with the principles and features described herein.
[0025] The use of the terms "a", "an", "the" and similar referents in the context of describing the invention (especially in the context of the appended claims) will be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The terms "comprising", "having", "including", and "containing" will be construed as open-ended terms (i.e., meaning "including, but not limited to") unless otherwise noted.
[0026] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. Note that the use of any and all examples or exemplary terms provided herein is intended only to better illustrate the present invention and is not intended to limit the scope of the present invention unless otherwise specified. In addition, unless otherwise specified, all terms defined in common dictionaries are not to be over-interpreted.
[0027] A magnetic device and a method for providing a magnetic device are described. The magnetic device includes a substrate, a Mn covering the substrate x N layer, a multilayer structure that is nonmagnetic at room temperature, and a first magnetic layer. Mn x The N layer has 2≤x≤4.75. The multilayer structure comprises alternating layers of Co and E, wherein E comprises at least one additional element including Al. The composition of the multilayer structure is Co 1-x E x , wherein x is in the range from 0.45 to 0.55. The first magnetic layer includes a Heusler compound. The first magnetic layer is in contact with the multilayer structure, and the first magnetic layer forms part of a magnetic tunnel junction.
[0028] Heusler compounds are formed by space group symmetry L2 1 (or D0 when they are deformed 22 ) defined by a unique structure. The properties of Heusler compounds strongly depend on the chemical ordering of the elements that make up the compound. Therefore, the fabrication of high-quality Heusler films usually requires high-temperature thermal treatments: for example, deposition at temperatures significantly above room temperature and / or thermal annealing at high temperatures (400°C or higher). Such high temperatures cause interdiffusion between layers within the MTJ stack that leads to poor MTJ performance and must therefore be avoided. Recently, we have disclosed highly textured, very smooth, high-quality ultrathin films of Heusler compounds that can be deposited using a non-magnetic chemical template layer without a thermal annealing process. The chemical template layer is preferably composed of a binary alloy of Co-Ga or Co-Ge or Co-Sn or Co-Al in a B1 structure (L1 0 The chemical template layers can be deposited at room temperature and are even chemically ordered in some cases (Co-Al) at room temperature or at significant annealing temperatures (above 400°C for Go-Ga and 200-300°C for Co-Sn). We find that ultrathin films of Heusler compounds deposited on these template layers are highly epitaxial, chemically ordered, high-quality films with excellent magnetic properties, including exceptionally high values of perpendicular magnetic anisotropy and square hysteresis loops (the remanent moment in zero magnetic field is close to the saturation moment). We attribute this to the B1 symmetry of the template layer and the L2 symmetry of the Heusler layer. 1 or D0 22 The Heusler compound can be selected from the group consisting of Mn 3.1-x Ge、Mn 3.1-x Sn and Mn 3.1-x Sb, wherein x is in the range from 0 to 1.1. Alternatively, the Heusler compound may be a ternary Heusler such as Mn 3.1-x Co 1.1-ySn, where x ≤ 1.2 and y ≤ 1.0. The chemical template layer requires an insulating MgO layer as a seed layer, which limits its utility in STT-MRAM applications because the switching current flows through the MTJ device. Here we show the conductive Mn x N (2.5≤x≤4) can be used as a seed layer for a chemical template layer that allows the growth of an ultrathin Heusler film whose magnetic moment is switchable via STT.
[0029] Mn nitride films are usually -9 The ultra-high vacuum chamber with a base pressure of Torr was used to deposit a 25 nm thick thermally oxidized SiO 2 The Si substrate was sequentially cleaned in a UV ozone chamber to remove any adsorbed organic matter, rinsed in a deionized water bath to remove water-soluble contaminants and particles, exposed to hot IPA vapor to remove water, and finally dried in a hot nitrogen oven at ~60°C. The Mn nitride seed layer was deposited on a 3×10 -3 The Mn nitride layer is deposited from a Mn metal target by reactive DC magnetron sputtering in a gas mixture of Ar and N2 at a pressure of 1000 torr. The relative ratio of Mn:N in the Mn nitride layer can be adjusted by adjusting the ratio of Ar and N 2 A mixture of sputtering gas N 2 Content to control (see Figure 1 ). The composition of the Mn nitride film is from a layer deposited on a graphite substrate and covered with Pt to prevent oxidation when exposed to the ambient environment Rutherford Backscattering (RBS) Determination of Mn Nitride Films. A graphite substrate containing primarily carbon (an element with a lower atomic number than nitrogen) allows the nitrogen content of the Mn nitride film to be determined to within ±0.5%. MnN films having compositions of interest in the present disclosure were prepared by varying the N content of the sputtering gas within a range of 10% to 20%. 2 The preferred composition is Mn x N, where 2.5≤x≤4. Alternatively, Mn nitride can be grown by sputtering from a MnN target.
[0030] Film roughness is an important parameter that must be minimized to obtain high-quality MTJs with ultrathin magnetic electrodes and tunnel barriers. 4 N films were deposited at different growth temperatures and then Ta layer covers to prevent Mn 4 Any oxidation of the N film due to ambient conditions. The film stack used for these series of films is Si / SiO 2 / Ta / Co 20 Fe 60 B20 / T G Next Mn 4 N / Ta, where T G = room temperature, 200° C., 300° C., 400° C. and 500° C. The film roughness was determined using atomic force microscopy (AFM). Figure 2 The root mean square surface roughness (r rms ). G Films deposited at ≤200°C showed R rms Therefore, Mn x N film (where 2.5≤x≤4) is then G The Mn nitride films were deposited at substrate temperatures ≤200°C. The composition dependence of the surface morphology of the Mn nitride films is shown in Figure 3 In. Here, Mn x N films were deposited at room temperature where x = 1, 2, 3, 3.76, 4, and 4.75. The film stacks for these series of films are Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / Mn x N For Mn:N ratios between 2 and 4, a R rms smooth films. The figure also summarizes the resistivity of these MnN films. The film resistivity was determined by a 4-point in-line probe technique close to the center of the sample. The spacing between the 4 contacts was ~1 mm, much smaller than the sample size. For films with Mn:N ratios between 1 and 2, the resistivity of the Mn nitride films increases sharply with decreasing N content. At higher Mn:N ratios ≥ 3, the resistivity of the MnN films is insensitive to composition. In addition, the resistivity of films with Mn:N ratios between 2 and 4 is comparable to that of metallic underlayers commonly used in magnetic tunnel junction stacks (e.g., the resistivity of Ti is 42 μΩ-cm and the resistivity of Ta is 95 μΩ-cm). In addition, the resistivity of the Mn nitride film is almost one-fifth of the TaN seed layer also used in the MTJ stack (e.g., deposited by reactive RF magnetron sputtering in argon with 10% N 2 The resistivity of the grown TaN film is reported to be ~700 μΩ-cm). Therefore, Mn nitride films are suitable for use within MTJ stacks.
[0031] X-ray diffraction (XRD) θ-2θ scans were measured on these films on a Bruker X-ray diffractometer with a GADDS area detector. These XRD measurements were performed in symmetric out-of-plane geometry and were sensitive to film texture. Figure 4 A set of XRD scans from these films are shown, and a single diffraction peak was observed in each case. All Mn x The N film has the desired (001) orientation. The 2θ position and intensity of the diffraction peak strongly depend on the composition of the Mn nitride film, indicating that Figure 5 The out-of-plane lattice constants of the Mn nitride films vary almost linearly with the Mn:N ratio. Moreover, for films with Mn:N ratios in the range of 2.5 to 4, their out-of-plane lattice constants are within ±2% of that of the typical tetragonal Heusler compound Mn. 3 The out-of-plane lattice constant of Sn and that of CoAl CTL are well matched. This lattice constant match promotes the growth of tetragonal Heusler compounds in the desired out-of-plane orientation. In addition, adjusting the Mn nitride composition provides the flexibility to tune the lattice mismatch by adjusting the Mn:N ratio.
[0032] The chemical template layer of CoAl was deposited at room temperature by ion beam deposition (IBD) or by DC magnetron sputtering. Mn x N films with x = 1, 2, 3, 3.76, 4, and 4.75. XRD measurements in out-of-plane geometry were performed to determine the Mn x Does the N film promote the necessary texture and alternating layer structure within the CoAl layer? XRD data are included Figure 6 and obtained from a film having a stack consisting of: Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / Mn x N / CoAl / Mn 3 Sb / MgO / In addition to the XRD peaks from the MnN layer drawn in the shaded area of the figure, for Mn other than x = 1 xTwo peaks associated with the CoAl layer were observed for all compositions of N. These CoAl peaks correspond to the (001) and (002) diffractions and demonstrate that the deposited CoAl layer has the desired (001) texture. The presence of the CoAl (001) superlattice peak clearly demonstrates the presence of alternating layering of Co and Al, which promotes ordering within the Heusler compound during its growth at room temperature.
[0033] The perpendicular magneto-optical Kerr effect (P-MOKE) signal as a function of applied field (H) was measured from the films in this series. Figure 7 P-MOKE loops from the sample in its deposited state and after annealing in a vacuum furnace at 300 °C for 30 min in an applied field of 1 T are shown. x N films also do not show hysteresis loops. x N film, a P-MOKE hysteresis loop was observed after the annealing process. The P-MOKE hysteresis loop shows that the ultrathin Thick Mn 3 The Sb Heusler layer is PMA. Interestingly, for Mn with x = 3 and 4 x N films, even in their as-deposited state, P-MOKE hysteresis loops from ultrathin Heusler layers were observed, making them the preferred Mn nitride compositions.
[0034] Figure 8 The determination of the Heusler compound (Mn 3 Thermal stability of the coercivity (Hc) of the P-MOKE hysteresis loop of Ge) and its effect on Mn 3 The film stack used in this study is Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / Mn 4 N / CoAl / Mn 3 Ge / MgO / Ta, among them and The films were deposited at room temperature and the P-MOKE hysteresis loops were measured in the as-deposited state and after successive annealing at 300°C, 350°C and 400°C for half an hour in an applied field of 1 T. Mn 3The Ge layer is stable and does not show a significant change in the coercivity of the layer even after annealing at 400 °C. Therefore, we conclude that the Ge layer can be grown on an amorphous substrate (Si / SiO 2 ) has sufficient thermal stability required to withstand the process conditions typically used during CMOS manufacturing.
[0035] Another type of substrate that is routinely used to evaluate the magnetic and switching properties of MTJ stacks is the CIPT substrate (CIPT stands for Current In-Plane Tunneling). These substrates are coated with a very smooth surface finish ( R rms ) Highly conductive W and TiN thickness layer of Si substrate. Fig. 9 A schematic diagram showing a typical material stack (sample number G1757-37) grown on a CIPT substrate. The material stack is: CIPT substrate / Ta / Co 20 Fe 60 B 20 / Mn 4 N / CoAl / Mn 3 Ge / MgO / Co 20 Fe 60 B 20 / Ta / [ Co / Pt] 3 / Ru / Co / Pt / [ Co / Pt] 4 / Pt / Ru. The seed layer disclosed herein Mn 4 N / CoAl promotes Heusler compounds with larger PMA Mn 3Growth of Ge. The Heusler compound is a magnetic storage electrode or a switchable magnetic layer. In some embodiments, the first magnetic layer including the Heusler compound can have a thickness less than 5 nm, a thickness less than 3 nm, or the thickness of one unit cell. The tunnel barrier used is preferably MgO with a (001) texture, but other (001)-oriented tunnel barriers such as CaO and LiF can also be used. Alternatively, Mg 1-z Al 2-z O 4 can be used as a tunnel barrier, -0.5 < z < 0.5. For example, MgAl 2 O 4 can be used as a tunnel barrier, and the lattice spacing of this tunnel barrier can be adjusted by controlling the Mg - Al composition, which can result in a better lattice match with the Heusler compound. The reference magnetic electrode covering the tunnel barrier can include, for example, Fe, CoFe alloy, or CoFeB alloy. By contacting the reference electrode with a synthetic antiferromagnet (SAF) structure, the magnetic moments of the reference electrodes are stabilized to a high magnetic field (i.e., making their coercivities significantly higher than that of the switchable magnetic layer). The SAF structure used here is Co / Pt] 3 / Ru / Co / Pt / Co / Pt] 4 。It should be noted that other SAF structures not described here can also be used. The capping layer can include Mo, W, Ta, Ru, Pt, or even a conductive nitride layer or a combination thereof. For better performance (i.e., improving the TMR or switching characteristics of the MTJ), an optional (second) magnetic layer or a so-called "polarization enhancement layer" can be advantageously employed. The optional second magnetic layer can include Fe, CoFe alloy, Co 2 FeAl, Co 2 MnSi, or another Heusler compound. The optional magnetic layer can be located on either side or even both sides of the tunnel barrier. The optional second magnetic layer can be in contact with the tunnel barrier. The capping layer can be in contact with the optional second magnetic layer. Current can be generated by applying a voltage between two magnetic electrodes separated by the tunnel barrier.
[0036] Fig.10 Shows the hysteresis loop measured for the sample after annealing it at 350 °C for 30 minutes in a high vacuum chamber with a 1 T field applied along the sample normal. These vibrating sample magnetometer (VSM) measurements are performed at room temperature with an externally applied magnetic field oriented along the sample normal. Switching of the SAF layer is observed in a field of ~3 to 4 kOe, but Mn 3The hysteresis loops of the Ge Heusler compound are not visible due to their low magnetic moment. The switching field of the Heusler compound was determined to be <300 Oe by current in-plane tunneling (CIPT) measurements (see Table 1). These measurements were performed on a commercial instrument provided by CAPRES A / S. The magnetic field was applied along the sample normal by positioning a permanent magnet above the sample, and the field strength was adjusted by changing the position of the magnet relative to the sample. The TMR of the sample was determined to be ~10%, and the resistance area product (RA) was ~25 Ω-(μm) 2 .
[0037] Table 1
[0038] sample Field [Oe] TMR [%] <![CDATA[RA[Ωμm 2 ]]]> G1757-37 ±300 8.4 25.4 ±450 8.7 25.4 ±750 9.7 25.4 ±1500 9.2 25.5 ±2100 8.7 25.4 ±2400 9.3 25.4 ±2790 9.4 25.4
[0039] The MTJ devices shaped like nanopillars were patterned by electron beam lithography with sizes ranging from 30nm to 250nm in diameter. The MTJ stack etch was terminated after nominally 10% of the CoAl layer was removed to minimize sidewall deposition. 2 There are a total of 256 devices on a single CIPT substrate of size. Fig.11 Yield distribution plots are shown as a plot of conductance versus device area for all patterned MTJ devices. These electrical tests were performed on a custom probe station. 80% of the MTJ devices showed the expected ~25Ω-μm 2 RA values. Also in the double logarithmic plot, the MTJ device conductance is linearly related to the device area. The solid line is a linear least squares fit to these data and has a slope of 1.07, close to the expected value of 1. The switching of the magnetic state by both field and current was probed for several working devices.
[0040] Fig.12 : is a transmission electron microscope image of an STT switchable MRAM device (device number 614) from another sample (sample G1746-39) containing a Heusler storage layer. This material stack is slightly different from the material stack detailed above: CIPT substrate / Ta / Co 20 Fe 60 B 20 / Mn 4 N / CoAl / Mn 3 Ge / MgO / Co 20 Fe 60 B 20 / Ta / [ Co / Pt] 2 / Ru / Co / Pt / [ Co / Pt] 4 / Pt / Ru. Prior to electron beam lithographic patterning into nanopillar MTJ devices, the deposited material stack was annealed at 350 °C for 30 min in a high vacuum chamber with a field of 1 T applied along the sample normal. The diameter of the MTJ device was determined to be 102 nm, in good agreement with its nominal diameter of 100 nm. The slight undercut in the device shape comes from the sidewall removal step. High-resolution images show the various layers comprising the deposited material stack. The CoAl layer has a bcc texture with a (001) orientation along the sample normal. Also, an expanded view of the area shows that the Mn 3 The Ge layer has a very similar structure to the underlying CoAl layer and grows with its tetragonal axes along the sample normal.
[0041] Fig.13 The resistance (R) versus applied field (H) loop measured from a 110 nm diameter (nominal) device (device number 501 and sample number G1757-37) with the field applied perpendicular to the substrate is shown. The RH loop is 50 mV sense voltage (V sense ) was measured in constant current mode. The switching between the low-resistance state and the high-resistance state is attributed to the rotation of the magnetic moment of the Heusler layer by applying an external magnetic field (see Fig.13 ). The Heusler layer switches sharply, while the SAF structure switches much more slowly (see data at fields < -2 kOe). The TMR of this device is consistent with the CIPT measurement of 9.6% on the blanket film. Fig.14 The bias voltage (V bias ) pulse (RV loop). The schematic on the right shows a pulse generator in series with the device to generate V bias pulse. The current flow direction is opposite to the V bias is the opposite. The resistance of the device switches to the threshold V bias Above, and the two states (see Fig.14 The resistance of the two illustrations in Figure 1 is similar to that of the RH loop ( Fig.13). This indicates that the magnetization of the Heusler layer switches between the same two states during STT switching as during magnetic field-induced switching. STT switching of the Heusler layer was also independently confirmed by determining the switching phase diagram, in which the threshold switching voltages for switching between the high resistance state to the low resistance state and the low resistance state to the high resistance state (i.e., the parallel magnetization state to the antiparallel magnetization state and the antiparallel magnetization state to the parallel magnetization state) were found to be strongly dependent on the applied magnetic field. Due to the lower integration time used in these measurements, the RV loop ( Fig.14 ) is higher than the point-to-point noise in the RH loop ( Fig.13 ) Point-to-point noise in the device. The current density J required for STT switching of the device using a 1 ms voltage pulse c ~6×10 5 Acm -2 This Jc is an order of magnitude lower than that of similar size devices with CoFeB switchable magnetic storage electrodes. This lower Jc is highly desirable as MTJ devices scale down to lithographic nodes below 20nm.
[0042] Fig.15 The probability of switching an MTJ device (device number 602 and sample number G1757-37) with a 100 nm (nominal) device diameter was measured as a function of a nanosecond voltage pulse. A schematic diagram of the measurement setup used is shown on the right. The MTJ device is first set to its low resistance state or high resistance state (parallel magnetization state or antiparallel magnetization state) by passing a 1 ms reset pulse through the device. Next, a switching voltage pulse (V p ) through the device. A total of 100 pulses were used and the probability of switching the MTJ device resistance was determined by reading the device resistance after each pulse. For lower V p , for any given V p The pulse width t at which the switching probability is 50% (50%) Increase.
[0043] Fig.16 Summarizes the switching current (I c ) and pulse width (t p ) relationship. These data are divided into two mechanisms, precessional (t p <~100ns) and thermally activated (t p >~1ms), see the figure on the left. The dashed line shows the fit of the macroscopic spin model (see D. Bedau et al, Appl. Phys. Lett. 97, 262502 (2010)). p The inverse of (for tp <~100ns) with I c changes linearly, indicating conservation of angular momentum (see Fig.16 right in the figure).
[0044] Some of the structures described herein may also be used in racetrack memory devices. In this case, the racetrack may include a substrate, an optional seed layer, a Mn x N / CoAl layers (where 2.5≤x≤4) and nanowires of the first magnetic layer of Heusler compounds. (For possible compositions of these layers, see above Fig. 9 Note that in track storage devices, normally there is no Fig. 9 The tunnel barrier and switchable magnetic layer shown; however, in this case, Fig. 9 The first magnetic layer shown would have a switchable rather than fixed magnetic moment.) The magnetic domain walls can be moved along the racetrack, as described in U.S. Patent 6,834,005. Data can be read from the racetrack (and stored in the racetrack) by interrogating (or changing) the orientation of the magnetic moment of the magnetic material between adjacent domain walls in the racetrack.
[0045] The various layers described herein may be deposited by any one or more of a variety of methods, including magnetron sputtering, electrodeposition, ion beam sputtering, atomic layer deposition, chemical vapor deposition, and thermal evaporation.
[0046] The present invention may be implemented in other specific forms without departing from its spirit or essential features. The described embodiments will be considered in all respects as illustrative only and not restrictive. Therefore, the scope of the present invention is represented by the appended claims rather than the preceding description. The equivalent meanings of the claims and all changes within the scope will be included within the scope.
[0047] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 763,123, filed in the U.S. Patent and Trademark Office on April 3, 2018, for "Efficient Predictive Circuit Simulator Based on Physics-Inspired Recurrent Neural Networks," and U.S. Patent Application No. 16 / 119,785, filed in the U.S. Patent and Trademark Office on August 31, 2018, for "Efficient Predictive Circuit Simulator Based on Physics-Inspired Recurrent Neural Networks," the entire disclosures of which are incorporated herein by reference.
Claims
1. A magnetic device, comprising: substrate; Mn coated on the substrate x N layers, where 2≤x≤4.75; A multilayer structure that is nonmagnetic at room temperature, the multilayer structure comprising alternating layers of Co and E, wherein E comprises at least one other element, the at least one other element comprising at least one of Ge, Ga, Sn and Al, wherein the composition of the multilayer structure is Co 1-y E y Indicates that y is in the range of from 0.45 to 0.55, the multilayer structure covers the Mn x N layers; and A first magnetic layer comprising a Heusler compound having perpendicular magnetic anisotropy, wherein The first magnetic layer is in contact with the multilayer structure, and the multilayer structure is x between the N layer and the first magnetic layer, and The first magnetic layer forms part of a magnetic tunnel junction. 2 . The magnetic device of claim 1 , wherein a magnetic moment of the first magnetic layer is perpendicular to an interface between the multilayer structure and the first magnetic layer. The magnetic device of claim 2 , wherein the first magnetic layer has a thickness less than 5 nm. The magnetic device of claim 2 , wherein the first magnetic layer has a thickness less than 3 nm. The magnetic device according to claim 2 , wherein the first magnetic layer has a thickness of one unit cell.
6. The magnetic device according to claim 1, wherein the Heusler compound is selected from the group consisting of Mn 3.1-z Ge、Mn 3.1-z Sn and Mn 3.1-z For the Sb group, z ranges from 0 to 1.
1.
7. The magnetic device of claim 1, wherein the Heusler compound is a ternary Heusler.
8. The magnetic device according to claim 7, wherein the ternary Heusler is Mn 3.1-s Co 1.1-t Sn, where s≤1.2 and t≤1.
0.
9. The magnetic device of claim 1, wherein E is Ge.
10. The magnetic device of claim 1, wherein E is Ga. 11 . The magnetic device of claim 1 , further comprising a tunnel barrier covering the first magnetic layer, thereby allowing current to pass through both the tunnel barrier and the first magnetic layer. 12 . The magnetic device of claim 11 , further comprising a second magnetic layer in contact with the tunnel barrier. The magnetic device of claim 12 , wherein the tunnel barrier is MgO.
14. The magnetic device of claim 12, wherein the tunnel barrier is Mg 1-z Al 2-z O4, of which -0.5 <z<0.5。 15. A method for providing a magnetic device, comprising: Use of the magnetic device according to claim 12 as a memory element. The method of claim 15 , wherein the storage element is a racetrack storage device.
17. A magnetic device, comprising: substrate; Mn coated on the substrate x N layers, where 2≤x≤4.75; A multilayer structure that is nonmagnetic at room temperature, the multilayer structure comprising alternating layers of Co and E, wherein E comprises at least one other element, the at least one other element comprising at least one of Ge, Ga, Sn and Al, wherein the composition of the multilayer structure is Co 1-x E x It means that x is in the range of 0.45 to 0.55, and the multilayer structure covers the Mn x N layers; A first magnetic layer including a Heusler compound, the first magnetic layer being in contact with the multilayer structure, the multilayer structure being located within the Mn x between the N layer and the first magnetic layer, wherein the first magnetic layer has a switchable magnetic moment and the Heusler compound has perpendicular magnetic anisotropy; a tunnel barrier covering the first magnetic layer; as well as a second magnetic layer in contact with the tunnel barrier, wherein The first magnetic layer, the tunnel barrier, and the second magnetic layer form at least part of a magnetic tunnel junction. 18 . The magnetic device of claim 17 , further comprising a cap layer in contact with the second magnetic layer. 19 . The magnetic device of claim 17 , wherein the first magnetic layer comprises Mn and an element selected from the group consisting of Sn, Sb, and Ge. 20 . The magnetic device of claim 17 , wherein the first magnetic layer further comprises Co.
Citation Information
Patent Citations
Shiftable magnetic shift register and method of using the same
US6834005B1
Methods For Manganese Nitride Integration
US20130292806A1
Magnetoresistive effect element and manufacturing method thereof
US20140077319A1